Role of the postnatal radial glial scaffold for the development of the dentate gyrus as revealed by reelin signaling mutant mice. Issue 8 (4th July 2013) - Brunne, Bianka; Franco, Santos; Bouché, Elisabeth; Herz, Joachim; Howell, Brian W.; Pahle, Jasmine; Müller, Ulrich; May, Petra; Frotscher, Michael; Bock, Hans H.
<x xml:space="preserve">Abstract</x> During dentate gyrus development, the early embryonic radial glial scaffold is replaced by a secondary glial scaffold around birth. In contrast to neocortical and early dentate gyrus radial glial cells, these postnatal glial cells are severely altered with regard to position and morphology in reeler mice lacking the secreted protein Reelin. In this study, we focus on the functional impact of these defects. Most radial glial cells throughout the nervous system serve as scaffolds for migrating neurons and precursor cells for both neurogenesis and gliogenesis. Precursor cell function has been demonstrated for secondary radial glial cells but the exact function of these late glial cells in granule cell migration and positioning is not clear. No data exist concerning the interplay between granule neurons and late radial glial cells during dentate gyrus development. Herein, we show that despite the severe morphological defects in the reeler dentate gyrus, the precursor function of secondary radial glial cells is not impaired during development in reeler mice. In addition, selective ablation of Disabled‐1, an intracellular adaptor protein essential for Reelin signaling, in neurons but not in glial cells allowed us to distinguish effects of Reelin signaling on radial glial cells from possible secondary effects based on defective granule cells positioning. GLIA 2013;61:1347–1363